Ethno-physics Studies on "Ani-Ani" Traditional Rice Harvesting Tools as Physics Learning Media - Akrom Chasani; Fakhruddin Fakhruddin (Jurnal Penelitian Pendidikan IPA, 2023)
The aim of this research is to analyze the physics concept of "ani-ani" a traditional rice harvesting tool as a physics learning material. With the aim of describing the results of the physics concept analysis study on the use of rice harvesting equipment to design physics learning materials in the study of the use of rice harvesting equipment. This research uses a qualitative descriptive method with data collection techniques in the form of observation, questionnaires and interviews and the data obtained is then analyzed, verified and reduced, then constructed into scientific knowledge and interpreted into high school physics concepts. The results obtained from this research are an analysis of the physical concepts of reaping or ani-ani starting from the mechanical advantages of using ani-ani, the pulling force exerted by the fingers and the pressure exerted by the fingers on the rice stalk so that the rice stalk is cut. The results of the concept analysis study were then used as draft physics learning materials for high school students. According to the relevant high school syllabus, namely basic competency 3.7 about particle dynamics (Newton's law) and 3.3 about static fluids (solid pressure).